Predictive power of selection tests on the academic performance of medical students - Calles Santoyo, María E.; De León Escobedo, Raúl; Salas Flores, Ricardo; González Pérez, Brian; Hernández Molina, Erick E. (Frontiers in Education, 2025)
This study analyzes the predictive power of various selection tests for admission to the bachelor’s degree in medical surgery at the Autonomous University of Tamaulipas. A retrospective cohort study with an analytical approach was conducted, evaluating 167 students of the 2022 cohort. Their performance in the first two school periods was compared with the results of admission tests such as the National Entrance Exam II of the National Evaluation Center for Graduate Education (CENEVAL EXANI-II), and other exams of the propaedeutic course. It was revealed that the CENEVAL EXANI-II test has a medium-high correlation (r = 0.588; p = 0.000) with academic performance in the first two terms although its predictive power is relatively low (R2 = 0.138, p = 0.001). Histology modules (r = 0.518; p = 0.000), and Module Final Exam (r = 0.472; p = 0.000) showed significant correlations but with lower predictive power. Differences in academic performance were identified according to gender and type of admission (selected vs. conditional). Although screening tests can predict academic success to some extent, their effectiveness is limited. Improved assessment methods are recommended to enhance the development of students in their medical training. This study provides the basis for future research on optimizing selection processes in medical education.